Estimation of land and manpower needs for year-round supply of green fodder (Super Napier) to dairy cattle through time studies and crop cutting experiments - Rao, M. V. Dharma; Reddy, B. Nageswara; Reddy, P. Pandu Ranga; Reddy, G. Sri Manjula (Journal of Scientific Agriculture, 2024)
The present study was undertaken to determine the land and manpower needed for the production of Super Napier fodder for the year-round feeding of dairy cattle present in Livestock Research Station, Mahanandi, Nandyal district, Andhra Pradesh through time studies and crop cutting experiments. The occasional activities of fodder production such as tillage, planting, irrigation and fertilizer application required 113.97 ± 7.31, 35.81 ± 0.98, 8.45 ± 0.31 and 0.56 ± 0.03 man-hours per acre, respectively, while the daily activities of fodder production such as harvesting of fodder, loading of fodder bundles, transport, chaffing and feeding took 5.64 ± 0.19, 1.86 ± 0.11, 0.24 ± 0.01, 0.93 ± 0.06 and 0.34 ± 0.01 man-hours per ton, respectively. Among the tillage operations, weeding required the most time (105.83 ± 6.90 man-hours per acre) and the application of an adjusted cultivator required the least time (0.64 ± 0.07 man-hours per acre). The cutting of planting material into stem cuttings and the harvesting of the planting material consumed the highest (16.52 ± 0.62 man-hours per acre) and lowest (3.97 ± 0.28 man-hours per acre) time, respectively, among the planting operations. There was a significant difference between two labourers of the same age in the application of adjusted cultivator (P < 0.01) and furrow irrigation (P < 0.05). The mean fresh yield of fodder in the farm was 16.73 ± 1.62 tons per acre per harvest or 100.40 ± 9.72 tons per acre per annum. Based on the results, it was concluded that one acre of cultivable land managed by a single person is sufficient for ensuring the year-round feeding of seven dairy animals under Super Napier fodder production.